STUDI TEGAKAN JENIS ULIN (Eusideroxylon zwageri Teijesm & Binnend) SEBAGAI SUMBER PENGHASIL BENIH DARI TEGAKAN BENIH TERSELEKSI DI KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - Heni Emawati, Yustinus Iriyanto, Zikri Azham (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
Research objectives: (1) to identify and select the location of seed stands as a potential source of seed ironwood in the Research Forest KHDTK Samboja with reference to No. Permenhut. P.72/Menhut-II/2009, (2) to determine the amount of parent ironwood trees in the prospective location of seed sources, including health conditions and dimensions (diameter and height of the tree), and (3) to map the identified ironwood seed stands and seed stands ironwood selectedThe study was conducted from April 2013 to July 2013 in Forest Area Special Purpose (KHDTK) Samboja Research Forest, East Kalimantan province. The selection of research methods ironwood identified seed stands and selected referring to No. Permenhut. P.72/Menhut-II/2009 on Amendment No. Permenhut. P.01/Menhut-II/2009 on the Implementation of Forest Plant Seed. While the data collected in the field is the position of the parent ironwood tree, tree dimensions (diameter and height), and the health of the tree (healthy, deformed roots, stem defects, defective canopy).The results based on studies in the field of seed stands of ironwood select locations identified in the Research Forest KHDTK Samboja area + / - 50 ha, located at Km 1.5 Samboja-Sepaku road axis. Grouping results based on tree diameter classes in the selected locations covering + / - 50 203 ha of ironwood trees identified as having the highest grade in the class diameter 28-35 cm diameter trees (51 trees or 25%), followed by further 44-51 cm diameter class (49 trees or 24%), and 60-67 cm diameter class (27 trees or 13%). While based on the individual's health condition grouping tree of 203 trees found there are 167 trees in good health (82%), tree with root defects there are 11 trees (5.4%), tree with disabilities tree trunk 13 (6%), and tree canopy with disabilities there are 12 trees (6%). The results also identify the existing 52 stem ironwood trees as a seed source in the Forest Research KHDTK Samboja. While the mother of 52 ironwood trees identified are then selected live 39 mother trees selected as a seed source ironwood in the Forest Research KHDTK Samboja.Based on these results it is the follow up management plans for selected seed stands ironwood this needs to be done by the Research Institute for Natural Resource Conservation Technology Samboja. Security activities of the threat of forest fires and illegal logging activities and research activities specifically related to phenology of flowering and fruiting period including produktifivitasnya mother plant is a major priority activities that need to be done going forward.